PERAN SITUS DAN TRADISI RITUAL KEAGAMAAN di Pulau-Pulau Kecil di Jepara - Sahri, Achmad (Sabda: Jurnal Kajian Kebudayaan, 2008)
Jepara Regency possesses 29 small islands; two islands are located near the mainland, these are Pulau Panjang and Pulau Mandalika. Both those islands having religious sites such as ulama graves and religious ritual traditions retained by surrounding society. The existence of religious sites and ritual traditions of these islands is effective in maintaining existing natural resources against the overexploitation, thus damages of natural resources can be avoided.